Method for manufacturing a composite member and composite member

JP7933303B2Active Publication Date: 2026-10-13TOHOKU UNIV +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021048892
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2021-03-23
Publication Date
2026-10-13
Estimated Expiration
2041-03-23

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、安価で効率良く、接合強度の高い複合部材を製造することができる複合部材の製造方法および複合部材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933303000004
    Figure 0007933303000004
  • Figure 0007933303000005
    Figure 0007933303000005
  • Figure 0007933303000006
    Figure 0007933303000006
Patent Text Reader

Abstract

To provide a method for producing a composite member capable of inexpensively and efficiently producing a composite member having high joining strength, and a composite member.SOLUTION: In a state where a resin-containing member 13 is pressed against a metallic porous film 12 formed on the surface of a metallic member 11, the metallic member 11 is heated to join the metallic member 11 and the resin-containing member 13. It is preferable that metal powder is collided against the surface of the metallic member 11 by a cold spray method to form the porous film 12.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a composite member and a composite member.

Background Art

[0002] As a method for joining metal and resin, in recent years, direct joining methods in which a resin is melted and fused to a metal surface have been actively researched (see, for example, Non-Patent Document 1). As such a direct joining method, for example, after forming fine pitting corrosion by chemical etching treatment or forming an uneven pattern by laser irradiation on the metal surface, a molten resin is filled into the fine structure using hot pressing or injection molding, and the resin is cooled and solidified, whereby a method of manufacturing a composite member firmly joined by an anchor effect has been proposed (see, for example, Patent Document 1, Non-Patent Documents 2 to 4).

Prior Art Documents

Non-Patent Documents

[0003]

Non-Patent Document 1

Non-Patent Document 2

Non-Patent Document 3

Non-Patent Document 4

[0004] [Patent Document 1] Japanese Patent Publication No. 2019-177704 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] However, the direct bonding method for manufacturing composite members described in Patent Document 1 and Non-Patent Documents 2 to 4 had the problem that when laser irradiation was used, the grip in the direction perpendicular to the hole formed by laser irradiation was weak, and the resin was prone to peeling off. In addition, there were problems that the number of parameters to be handled in controlling the laser irradiation was large, the manufacturing process was complicated, and the equipment was expensive. Furthermore, when chemical etching was used, it was necessary to repeat pre-cleaning such as washing and degreasing of the metal surface when immersing in the etching solution multiple times, and cleaning treatment and waste liquid treatment using chemical solutions were also necessary, resulting in poor manufacturing efficiency.

[0006] This invention has been made in view of these problems, and aims to provide a method for manufacturing composite members and a composite member that can produce composite members inexpensively, efficiently, and with high bonding strength. [Means for solving the problem]

[0007] To achieve the above objective, the method for manufacturing a composite member according to the present invention is characterized by bonding the metal member and the resin-containing member by pressing the resin-containing member against a porous metal film formed on the surface of the metal member and heating the metal member.

[0008] The composite member according to the present invention comprises a metal member, a porous film formed on the surface of the metal member, and a resin-containing member provided on the side of the porous film opposite to the metal member, wherein the metal member and the resin-containing member are joined together by a portion of the resin-containing member entering into the voids of the porous film.

[0009] The method for manufacturing a composite member according to the present invention can suitably manufacture the composite member according to the present invention. In the method for manufacturing a composite member according to the present invention, a resin-containing member can be melted or softened by heating a metal member and allowed to penetrate into the voids of the porous film. At this time, since the voids of the porous film are not oriented in one direction like holes formed by laser irradiation, the resin-containing member does not easily peel off, and a composite member with high bonding strength can be manufactured.

[0010] The method for manufacturing a composite member according to the present invention may be used to form a porous film by any means, but it is particularly preferable to form the porous film by impacting metal powder onto the surface of the metal member using a cold spray method. By using the cold spray method, oxidation and decomposition of the raw material metal powder are almost eliminated, and a porous film containing many pores can be formed with the metal powder particles well bonded together. By forming a porous film using the cold spray method, expensive equipment such as that used when laser irradiation is not required is not needed, and composite members can be manufactured at low cost. Furthermore, the cold spray method allows for the formation of a porous film over a wide area in a short time, and since there is no need for cleaning or wastewater treatment as when chemical etching is used, composite members can be manufactured efficiently in a short time.

[0011] In the method for manufacturing a composite member and the composite member according to the present invention, the metal member and the porous film may be made of the same metal or of different metals. The metal member may be made of any metal, for example, aluminum or an aluminum alloy. The porous film may be made of any metal, such as aluminum, an aluminum alloy, stainless steel, titanium, or a titanium alloy, but if it is formed by a cold spray method, it is preferable that it be made of titanium or a titanium alloy. In this case, a strong porous film can be formed by using titanium powder or a titanium alloy as the metal powder.

[0012] The manufacturing method for the composite member according to the present invention may involve heating the metal member by friction while pressing it toward the resin-containing member, with the resin-containing member in contact with the porous film. In this case, for example, friction stir welding (FSW) can be used to join the metal member and the resin-containing member by rotating and pressing a cylindrical joining tool against the surface of the metal member from the opposite side of the porous film.

[0013] The present invention relates to a method for manufacturing a composite member and a composite member, in which the resin-containing member may consist of any material depending on the required properties and application, for example, a thermoplastic resin material or a thermosetting resin material before heat curing. The resin-containing member may consist only of resin, or a part of it may be resin. When the resin-containing member contains a thermoplastic resin material, it is preferable to heat the metal member at a temperature lower than the melting point of the thermoplastic resin material. In this case, the resin-containing member can be joined without melting, and the composite member can be manufactured relatively easily. Examples of thermoplastic resin materials include high-strength PEEK (polyether ether ketone) or PA6 (polyamide 6). When the resin-containing member contains a thermosetting resin material before heat curing, it is preferable to heat the metal member at a temperature higher than the melting point of the thermosetting resin material. In this case, the resin-containing member may consist of a thermosetting member having a fibrous reinforcing material and resin, such as a prepreg.

[0014] In the method for manufacturing a composite member and the composite member according to the present invention, the porous film preferably has a porosity of 4% or more, and more preferably 30% or less. Furthermore, the porous film preferably has a film thickness of 25 μm or more, and more preferably 280 μm or less. In these cases, the strength of the joint between the metal member and the resin-containing member is high, and the joined metal member and resin-containing member are difficult to separate. Furthermore, the porous film preferably has a porosity of 6% or more, and more preferably 27% or less. Furthermore, the porous film preferably has a film thickness of 35 μm or more, and more preferably 150 μm or less. In these cases, the strength of the porous film is further increased, making it particularly difficult for the joined metal member and resin-containing member to separate. [Effects of the Invention]

[0015] According to the present invention, it is possible to provide a method for manufacturing composite members and a composite member that can be manufactured inexpensively, efficiently, and with high bonding strength. [Brief explanation of the drawing]

[0016] [Figure 1] The present invention provides a side view showing a method for manufacturing a composite member according to an embodiment of the present invention, in which (a) a resin-containing member is pressed against a metal member and heated with a heater or the like to join the metal member and the resin-containing member, (b) a perspective view showing a method for joining a metal member and a resin-containing member using friction stir welding (FSW) by heating the metal member with frictional heat, and (c) a side view of the joining method in (b). [Figure 2] The images show, on the left, an optical microscope image of a cross-section near the bonding interface of a composite member manufactured by the manufacturing method of an embodiment of the present invention, for each metal powder used during the formation of the porous film and for each film formation condition of the porous film, as well as a graph (right) showing the porosity of the porous film, the porosity after penetration by the resin-containing member (Filled by PEEK), and the filling rate of the resin-containing member. [Figure 3]For the composite member manufactured by the method for manufacturing a composite member according to the embodiment of the present invention, this is an optical micrograph of the cross section near the bonding interface (left figure) for each metal powder used in forming the porous film and each film formation condition of the porous film, and a graph (right figure) showing the porosity of the porous film (Porosity), the porosity infiltrated by the resin-containing member (Filled by PEEK), and the infiltration rate of the resin-containing member (Filling rate). [Figure 4] For the composite member manufactured by the method for manufacturing a composite member according to the embodiment of the present invention, this is an optical micrograph of the cross section near the bonding interface (left figure) for each metal powder used in forming the porous film and each film formation condition of the porous film, and a graph (right figure) showing the porosity of the porous film (Porosity), the porosity infiltrated by the resin-containing member (Filled by PEEK), and the infiltration rate of the resin-containing member (Filling rate). [Figure 5] For the composite member of the comparative example of the method for manufacturing a composite member according to the embodiment of the present invention, which is manufactured only by blast treatment without forming a porous film, this is an optical micrograph of the cross section near the bonding interface when the alumina particles used for the blast treatment are (a) #24, (b) #60, and (c) #120. [Figure 6] This is a graph showing the relationship between the porosity of the porous film and the tensile shear strength of the composite member manufactured by the method for manufacturing a composite member according to the embodiment of the present invention. [Figure 7] For the composite member manufactured by the method for manufacturing a composite member according to the embodiment of the present invention, these are the optical micrograph of the cross section near the bonding interface and the film thickness of the porous film, for each scanning speed (ts) during formation of the porous film and for each case with or without blast treatment. [Figure 8] This is a graph showing the relationship between the film thickness of the porous film and the tensile shear strength of the composite member shown in Figure 7. [Figure 9] This is a graph showing the relationship between the film thickness of the porous film and the tensile shear strength of a composite member that is manufactured by the method for manufacturing a composite member according to the embodiment of the present invention and has a larger porosity of the porous film than the composite member shown in Figure 7. [Figure 10]In a comparative example of the method for manufacturing a composite member according to the embodiment of the present invention, an optical micrograph of a cross section near the bonding interface of a composite member produced by filling molten resin by hot press onto the surfaces of: (a) a blast-treated metal member without forming a porous film, (b) a metal member with pores formed at an area ratio of 40% by laser irradiation, and (c) a metal member with pores formed at an area ratio of 70% by laser irradiation. [Figure 11] Regarding the method for manufacturing a composite member according to the embodiment of the present invention: (a) a perspective view showing a test method of a tensile test for examining the strength of a porous film, and (b) an optical micrograph of a cross section of the porous film formed for the tensile test. [Figure 12] A graph showing the relationship between the thickness of the porous film and the tensile strength, obtained by the tensile test shown in FIG. 11(a). [Figure 13] Regarding the method for manufacturing a composite member according to the embodiment of the present invention: (a) the void ratio distribution of the porous film when the gas pressure of the compressed gas during metal powder spraying by the cold spray method is 312 kPa, (b) a scanning electron micrograph of the cross section of the porous film, (c) the void ratio distribution of the porous film when the gas pressure is 483 kPa, (d) a scanning electron micrograph of the cross section of the porous film, (e) the void ratio distribution of the porous film when the gas pressure is 620 kPa, and (f) a scanning electron micrograph of the cross section of the porous film. [Figure 14] A graph showing the relationship between the gas pressure of the compressed gas during metal powder spraying by the cold spray method and the tensile strength of the porous film, obtained by the tensile test shown in FIG. 11(a). [Mode for Carrying Out the Invention]

[0017] Hereinafter, embodiments of the present invention will be described based on the drawings, examples and the like. FIGS. 1 to 14 show the method for manufacturing a composite member and the composite member according to the embodiment of the present invention. As shown in Figure 1, the manufacturing method of the composite member according to the embodiment of the present invention first involves forming a metallic porous film 12 on the surface of the metal member 11. At this time, the porous film 12 may be formed by any method, but in the specific example shown in Figure 1, the porous film 12 is formed by impacting the surface of the metal member 11 with metal powder using a cold spray method. The metal member 11 is plate-shaped, and it is preferable to form the porous film 12 on one of its surfaces.

[0018] The metal member 11 and the porous film 12 may be made of the same metal or different metals. The metal member 11 may be made of any metal, for example, aluminum or an aluminum alloy. The porous film 12 may also be made of any metal. For example, titanium powder or titanium alloy powder may be used as the metal powder, and a strong porous film 12 made of titanium or a titanium alloy may be formed by a cold spray method.

[0019] After forming the porous film 12, the metal member 11 and the resin-containing member 13 are joined by heating the metal member 11 while the resin-containing member 13 is pressed against it. At this time, the resin-containing member 13 may be made of any material depending on the required properties and application. The resin-containing member 13 may be made of resin only, or part of it may be resin. For example, the resin-containing member 13 may be made of a thermoplastic resin material such as high-strength PEEK (polyether ether ketone) or PA6 (polyamide 6), or it may be made of a thermosetting member having a fibrous reinforcing material and resin, such as a prepreg.

[0020] The method for heating the metal member 11 can be any method. For example, as shown in Figure 1(a), the metal member 11 may be heated with a heater while the resin-containing member 13 is pressed against it. Alternatively, as shown in Figures 1(b) and (c), the resin-containing member 13 may be in contact with the porous film 12, and friction stir welding (FSW) may be used to heat the metal member 11 by rotating and pressing a cylindrical joining tool 21 against the surface of the metal member 11 opposite to the porous film 12, thereby generating frictional heat. Generally, the joining tool 21 for friction stir welding has a cylindrical shoulder 21a with a protruding probe 21b in the center. However, it is preferable that the probe 21b protrudes very little in order to suppress deformation of the metal member 11 and to make the joining interface as flat as possible.

[0021] By heating the metal member 11 in this way, the resin-containing member 13 can be melted or softened and allowed to enter the voids in the porous film 12. This makes it possible to manufacture a composite member according to an embodiment of the present invention, in which the metal member 11 and the resin-containing member 13 are joined together. When heating the metal member 11, if the resin-containing member 13 contains a thermoplastic resin material, the resin-containing member 13 can be joined without melting by heating it at a temperature lower than its melting point, making it possible to manufacture a composite member relatively easily.

[0022] According to the manufacturing method for composite members of the embodiment of the present invention, by utilizing the cold spray method, oxidation and decomposition of the raw material metal powder are almost eliminated, and a porous film 12 containing many pores can be formed with the metal powders well bonded together. Since the voids in the porous film 12 are not oriented in a single direction like holes formed by laser irradiation, the resin-containing member 13 does not easily peel off, and a composite member with high bonding strength can be manufactured.

[0023] Furthermore, by forming the porous film 12 using the cold spray method, expensive equipment is not required, as is the case when laser irradiation is used, and composite materials can be manufactured at a low cost. In addition, the cold spray method allows for the formation of the porous film 12 over a wide area in a short time, and since there is no need for cleaning or waste liquid treatment as is required when chemical etching is used, composite materials can be manufactured efficiently in a short time. [Examples]

[0024] In the manufacturing method of the composite member according to the embodiment of the present invention shown in Figures 1(b) and (c), a porous film 12 was formed by the cold spray method, and then the metal member 11 and the resin-containing member 13 were joined using friction stir welding (FSW). As the metal member 11, a rolled material of A5052 aluminum alloy was used. The metal member 11 is a rectangular plate that is long in the rolling direction, with a length of 200 mm, a width of 50 mm, and a thickness of 5 mm. In addition, the metal member 11 was roughened by spraying alumina powder (particle size φ600~700 μm (#40), φ200~250 μm (#60), φ90~120 μm (#120)) at a pressure of 0.3 MPa onto one surface (joining surface). As the resin-containing member 13, a thermoplastic resin material PEEK was used. The resin-containing member 13 is in the shape of a rectangular plate, with a length of 200 mm, a width of 50 mm, and a thickness of 5 mm.

[0025] A low-pressure cold spray apparatus (INOVATI KM-CDS 3.0) was used to form the porous film 12 by the cold spray method. The metal powders shown in Table 1 were used in the cold spray method. Table 1 also shows the film formation conditions for each metal powder [pre-treatment (Blast) or absence, powder feed rate, compressed gas pressure, process gas temperature, and spray nozzle traverse speed].

[0026] [Table 1]

[0027] As a pretreatment, the bonding surface of the metal member 11, after surface roughening, was subjected to blasting with alumina particles (#24). He gas was used as the process gas. In addition, the traverse speed was varied as shown in Table 1 to control the porosity and thickness of the porous film 12. Furthermore, in some cases, heat treatment was performed after film formation to improve the adhesion between the metal member 11 and the porous film 12. The heat treatment was performed in an air atmosphere using an electric muffle furnace. The heat treatment temperature and holding time were 500°C and 30 min for Al powder, and 600°C and 4 h for Ti-20, Ti-45, Ti-20+Ti-45, and Ti-20+Al2O3 powder (only Ti-20, in some cases, 600°C and 2 h or 14 h), in all cases, with air cooling.

[0028] A high-rigidity friction stir welding apparatus (TU-01, manufactured by Nitto Seiki Co., Ltd.) was used to join the metal member 11 and the resin-containing member 13. The overlap width between the metal member 11 and the resin-containing member 13 was set to 20 mm, and a joining tool 21 made of SKD61 was used. The joining tool 21 has a cylindrical shoulder 21a with a tool diameter of 15 mm, from which a probe 21b with a diameter of 5 mm protrudes 1.4 mm. The scanning speed of the joining tool 21 during joining was set to 10.0 mm / s, the rotation speed of the joining tool 21 was set to 1200 rpm, the insertion depth of the joining tool 21 into the metal member 11 was set to 1.1 mm, and the forward angle of the joining tool 21 was set to 3°.

[0029] The optical microscope images of the cross-section near the bonding interface of a composite member manufactured by forming a porous film 12 using each metal powder shown in Table 1 and bonding a metal member 11 (Al alloy) and a resin-containing member (PEEK) 13 are shown in the left figures of Figures 2-4, for each metal powder and porous film 12 deposition condition. "HT" indicates that the porous film 12 was heat-treated after deposition. "BL (Blast less)" indicates that the porous film 12 was not blast-treated before deposition.

[0030] From each optical microscope image, the porosity of each porous film 12 and the porosity filled by the resin-containing member 13 (Filled by PEEK) were measured using the point method, and the filling rate of the resin-containing member 13 was calculated from each porosity. The results are shown in the right-hand figures of Figures 2 to 4. The horizontal axis in each figure represents the ratio of the depth of the porous film 12 from the surface on the resin-containing member 13 side, where 0% is the interface between the porous film 12 and the resin-containing member 13, and 100% is the interface between the porous film 12 and the metal member 11. In addition, the average thickness and porosity of each porous film 12 were determined from each optical microscope image and are shown in Table 2.

[0031] [Table 2]

[0032] As shown in Figures 2-4 and Table 2, the resin-containing member 13 penetrates to some extent into the voids within the porous film 12. This was confirmed to occur even with porous films 12 that have a low porosity, such as SUS316L. Furthermore, it was confirmed that the penetration rate gradually decreases as the distance from the surface of the porous film 12 to the resin-containing member 13 increases. From this, it is considered that there is a certain limit to the penetration depth of the resin-containing member 13.

[0033] For comparison, a rolled A5052 aluminum alloy (without surface roughening or pretreatment) was used as the metal member 11, and the metal member 11 and the resin-containing member (PEEK) 13 were joined by friction stir welding without forming a porous film 12. As a result, it was confirmed that the resin-containing member 13 peeled off from the metal member 11 immediately after joining, making it almost impossible to join them.

[0034] Furthermore, for comparison, a composite member was manufactured by using a metal member 11 made from a rolled A5052 aluminum alloy whose surface was blast-treated with alumina particles (#24, #60, #120), and by friction stir welding to bond the metal member 11 and the resin-containing member (PEEK) 13 without forming a porous film 12. An optical microscope image of the cross-section near the bonding interface of this composite member is shown in Figure 5. As shown in Figure 5, it was confirmed that the resin-containing member 13 penetrated into the interior of the fine uneven structure on the surface of the metal member 11 formed by blast treatment, and that the metal member 11 and the resin-containing member 13 were in close contact without any gaps.

[0035] Next, tensile shear tests were performed on each of the manufactured composite members. The tests were conducted using a universal testing machine (INSTRON) at room temperature with a crosshead speed of 1.0 mm / min. For the tests, strip-shaped test pieces with a width of 20-25 mm were cut perpendicular to the joint direction from each composite member. In addition, three test pieces were cut from each composite material, and tensile shear tests were performed on each. The tensile shear strength of each composite material was calculated by averaging the obtained breaking loads divided by the joint area. The tensile shear strengths of each composite material are shown in Table 3.

[0036] [Table 3]

[0037] For comparison, a tensile shear test was also performed on a composite member without the porous film 12 shown in Figure 5. The results showed that the tensile shear strength was 7.9 to 8.7 MPa, and it was confirmed that the strength decreased as the surface of the metal member 11 became smoother. As shown in Table 3, the composite member with the porous film 12 had a tensile shear strength of 9.62 to 15.8 MPa, confirming that it was stronger than the composite member without the porous film 12.

[0038] Furthermore, observation of the fracture surfaces after tensile shear tests revealed that porous films 12 formed using Al, Ti-20, Ti-45, Ti-20+Ti-45, and Ti-20+Al2O3 powders fractured at the interface between the metal member 11 and the porous film 12. Additionally, those using Ti-45 powder and heat treatment fractured within the porous film 12. Furthermore, those using powders other than Ti-45 powder and heat treatment, or those using SUS316L powder, fractured at the interface between the porous film 12 and the resin-containing member 13.

[0039] For composite members that fractured at the interface between the porous film 12 and the resin-containing member 13 during tensile shear tests, the relationship between the porosity of the porous film 12 and the tensile shear strength was determined and is shown in Figure 6. As shown in Figure 6, it was confirmed that the tensile shear strength gradually increased as the porosity increased. Furthermore, even with a porosity of about 6.8%, the composite member had a tensile shear strength of about 12 MPa, confirming that it possessed sufficiently high strength.

[0040] Next, to investigate the relationship between the thickness of the porous film 12 and its strength, a porous film 12 was formed using Ti-20 powder at various scanning speeds (traversal speed; ts), and the tensile shear strength was measured for the composite members that had undergone heat treatment after film formation. The measurements were performed on composite members using metal members 11 that had undergone blast treatment as a pretreatment, and on composite members using metal members 11 that had not undergone blast treatment. The thickness of the porous film 12 was also varied by changing the scanning speed. Figure 7 shows an optical microscope image of the cross-section near the bonding interface of the composite member that was measured, as well as the thickness of the porous film 12. Figure 8 shows the relationship between the thickness of the porous film 12 and the tensile shear strength.

[0041] As shown in Figures 7 and 8, the tensile shear strength increases with increasing thickness of the porous film 12, but it was confirmed that it saturates to a certain strength at a certain film thickness. Furthermore, even with a film thickness of 38 μm, the porous film 12 had a tensile shear strength of 12 MPa or more, confirming that it possessed sufficiently high strength.

[0042] To investigate the effect of differences in the porosity of the porous film 12 on the relationship between the film thickness and strength of the porous film 12, porous films 12 were formed using Ti-20 + Ti-45 powder at various scanning speeds, and the tensile shear strength of the composite members, which were heat-treated after film formation, was measured in the same manner as in Figures 7 and 8. The relationship between the film thickness of the porous film 12 and the tensile shear strength is shown in Figure 9. Note that the porous film 12 formed using Ti-20 + Ti-45 powder has a higher porosity than the one formed using Ti-20 powder.

[0043] As shown in Figure 9, similar to Figure 8, it was confirmed that the tensile shear strength increased as the thickness of the porous film 12 increased, and that it saturated at a certain thickness. However, compared to Figure 8, it was confirmed that the saturation strength was higher and the thickness at which the saturation strength was reached was also larger. This is thought to be because the shear strength of the resin-containing member 13 is ensured as the porosity increases.

[0044] [Comparative example using laser irradiation] As described in Non-Patent Literature 4, a composite member was manufactured by forming numerous pores on the surface of a metal member 11 by laser irradiation, filling the surface of the metal member 11 with molten resin by hot pressing, and then cooling and solidifying the resin. A Ti alloy was used as the metal member 11, and PEEK was used as the resin. The diameter of the pores formed by laser irradiation was approximately 270 μm, and the hot pressing temperature was 300°C. Optical microscope images of the cross-section near the bonding interface of the composite member when the pore area ratio on the surface of the metal member 11 was 40% and 70%, respectively, are shown in Figures 10(b) and (c), respectively.

[0045] For comparison, Figure 10(a) shows an optical microscope image of a cross-section near the bonding interface of a composite member manufactured using a metal member 11 that was blast-treated with alumina particles (diameter 250 μm) without laser irradiation. As shown in Figures 10(a) to (c), it was confirmed that in both composite members, the resin penetrated into the irregularities and pores on the surface of the metal member 11, and that the metal member 11 and the resin were in close contact without any gaps. Furthermore, as shown in Figures 10(b) and (c), it was confirmed that the pores formed by laser irradiation extended only in a direction perpendicular to the surface of the metal member 11.

[0046] Tensile shear tests were performed on the composite members shown in Figures 10(a) to (c) in the same manner as in Example 1. As a result, the tensile shear strength was 11 MPa for the blast-treated member shown in Figure 10(a), 25 MPa for the member with a 40% pore area ratio due to laser irradiation shown in Figure 10(b), and 51 MPa for the member with a 70% pore area ratio due to laser irradiation shown in Figure 10(c). Comparing these results with those shown in Table 3, it can be seen that the composite members using laser irradiation have greater tensile shear strength than those in which the porous film 12 was formed by the cold spray method. However, as shown in Figures 10(b) and (c), the holes formed by laser irradiation extend only in a direction perpendicular to the surface of the metal member 11. Therefore, the composite members using laser irradiation have weaker resin adhesion in the direction perpendicular to the surface of the metal member 11, and are considered to be weaker against delamination than those in which the porous film 12 was formed by the cold spray method. [Examples]

[0047] As the metal member 11, a rolled material of A5052 aluminum alloy was used, and as the resin-containing member 13, PA6 thermoplastic resin was used. Following the formation of a porous film 12 by cold spraying using the manufacturing method of the composite member according to the embodiment of the present invention shown in Figures 1(b) and (c), the metal member 11 and the resin-containing member 13 were joined using friction stir welding (FSW). Ti powder was used in the cold spraying method. In friction stir welding, the scanning speed of the joining tool 21 was set to 13 mm / s, the rotation speed of the joining tool 21 to 1000 rpm, and the insertion depth of the joining tool 21 into the metal member 11 was set to 1.0 mm. Other manufacturing conditions were the same as in Example 1.

[0048] A tensile shear test was performed on the manufactured composite member in the same manner as in Example 1. As a result, the tensile shear strength was 10 MPa, which was confirmed to be higher than that of the composite member without the porous film 12 shown in Figure 5. The porous film 12 of the manufactured composite member had a thickness of approximately 130 μm. [Examples]

[0049] Using a rolled A5052 aluminum alloy as the metal member 11 and PA6 as the resin-containing member 13, a porous film 12 was formed by cold spraying using the manufacturing method of the composite member according to the embodiment of the present invention shown in Figure 1(a). Then, with the resin-containing member 13 pressed against it, the metal member 11 was heated with a heater to bond the metal member 11 and the resin-containing member 13. The resin-containing member 13 was pressed against the metal member 11 with a hand press, and the heating temperature of the metal member 11 was set to 300°C.

[0050] A tensile shear test was performed on the manufactured composite member in the same manner as in Example 1. As a result, the tensile shear strength was 7 MPa or higher. The porous film 12 of the manufactured composite member had a film thickness of approximately 270 μm. [Examples]

[0051] To investigate the relationship between the thickness and strength of the porous film 12, a porous film 12 was formed by the cold spray method using the manufacturing method of the composite member according to an embodiment of the present invention, and then a tensile test was performed on the porous film 12. As shown in Figure 11(a), an A5052 aluminum alloy was used as the metal member 11 in the tensile test. The metal member 11 was cylindrical in shape, with a diameter of 25 mm and a length of 40 mm. In the cold spray method, Ti-45 powder with a particle size of 1 to 45 μm was used, the compressed gas pressure was set to 620 kPa, the process gas temperature to 427 °C, and the spray nozzle scanning speed to 500 mm / s. Furthermore, porous films 12 of various thicknesses were formed by changing the number of layers in the cold spray method. The porosity of the porous film 12 was 6% or more in all cases. An example of an optical microscope image of a cross-section of the porous film 12 formed on one surface of the metal member 11 is shown in Figure 11(b).

[0052] As shown in Figure 11(a), in the tensile test, an adhesive 31 was applied to the surface of each formed porous film 12, and then a base material 32 made of A5052 aluminum alloy, the same size as the metal member 11, was bonded to it. The adhesive 31 used was "3M® Scotch-Weld® DP-460 Off-White (3M Japan Limited)". After bonding with the adhesive, the metal member 11 and the base material 32 were pulled to determine the tensile strength of each porous film 12. The results of the tensile test are shown in Figure 12.

[0053] As shown in Figure 12, tensile tests confirmed that when the thickness of the porous film 12 was 150 μm or less, it fractured inside the adhesive, and the tensile strength was 35 MPa or more. Furthermore, when the thickness of the porous film 12 was 150 μm or more, it fractured inside the porous film 12 near the metal member 11, and the tensile strength was 35 MPa or less. From these results, it can be said that by making the porous film 12 150 μm or less, the strength of the porous film becomes at least 35 MPa or more, making it difficult for the bonded metal member 11 and resin-containing member 13 to separate when the composite member is manufactured. [Examples]

[0054] To investigate the relationship between the porosity and strength of the porous film 12, the porous film 12 was formed and subjected to tensile testing in the same manner as in Example 4. In the cold spray method, porous films 12 with different porosities were formed by changing the gas pressure of the compressed gas during metal powder spraying to 312 kPa, 483 kPa, and 620 kPa. Figure 13 shows the relationship between the distance of the porous film 12 from the surface of the metal member 11 and the porosity, as well as scanning electron microscope images of the cross-section of the porous film 12 at each gas pressure.

[0055] As shown in Figure 13, when the gas pressure is 312 kPa, the porosity of the porous film 12 is approximately 4% to 9%, with an average of 5.58%. At 483 kPa, the porosity of the porous film 12 is approximately 8% to 16%, with an average of 12.4%. At 620 kPa, the porosity of the porous film 12 is approximately 6% to 20%, with an average of 13.5%. It was confirmed that the porosity of the porous film 12 increases with increasing gas pressure. This is thought to be because, at low gas pressure, the impact force of the metal powder is small, so larger particles do not bond together, and only smaller metal powders accumulate and fill the gaps between particles. At high gas pressure, the impact force of the metal powder is large, so larger particles bond together, and gaps are more likely to form between them.

[0056] Figure 14 shows the results of tensile tests on each porous film 12 with different gas pressures. As shown in Figure 14, the tensile tests confirmed that at gas pressures of 483 kPa and 620 kPa, the film fractured inside the adhesive, and the tensile strength was 40 MPa or higher. At a gas pressure of 312 kPa, the film fractured inside the porous film 12, and the tensile strength was approximately 32 MPa. From these results, it can be said that by setting the gas pressure to 483 kPa or higher, that is, by setting the porosity of the porous film 12 to 6% or higher and the average porosity to 12% or higher, the strength of the porous film becomes at least 40 MPa or higher, making it difficult for the joined metal member 11 and resin-containing member 13 to separate when the composite member is manufactured. [Explanation of Symbols]

[0057] 11 Metal components 12 Porous membrane 13 Resin-containing components 21 Joining Tools 21a Shoulder 21b probe 31 Adhesive 32 Base material

Claims

1. A method for manufacturing a composite member, characterized by pressing a resin-containing member (excluding those consisting of a metal layer and an adhesive layer) onto a porous metallic film formed on the surface of a metal member, having a void ratio of 4% or more and a film thickness of 25 μm to 280 μm, and then heating the metal member to join the metal member and the resin-containing member.

2. A method for manufacturing a composite member according to claim 1, characterized in that metal powder is impacted onto the surface of the metal member by a cold spray method to form the porous film.

3. A method for manufacturing a composite member according to claim 1 or 2, characterized in that the composite member is made of a metal different from the metal member and the porous film.

4. With the resin-containing member in contact with the porous film, the metal member is pressed toward the resin-containing member and heated by friction. A method for manufacturing a composite member as described in any one of claims 1 to 3.

5. The method for manufacturing a composite member according to any one of claims 1 to 4, characterized in that the resin-containing member is a thermoplastic resin material.

6. A method for manufacturing a composite member according to any one of claims 1 to 4, characterized in that the resin-containing member comprises a thermosetting member having a fibrous reinforcing material and a resin.

7. Metal components, A porous film formed on the surface of the metal member, having a void ratio of 4% or more and a film thickness of 25 μm or more and 280 μm or less, The porous film has a resin-containing member (excluding one consisting of a metal layer and an adhesive layer) provided on the side opposite to the metal member, The resin-containing member is joined to the metal member by a portion of the resin-containing member entering the voids in the porous film. Characteristic composite material.

8. The composite member according to claim 7, characterized in that it is made of a metal different from the metal member and the porous film.

9. The composite member according to claim 7 or 8, characterized in that the resin-containing member is a thermoplastic resin material.

10. The composite member according to claim 7 or 8, characterized in that the resin-containing member comprises a thermosetting member having a fibrous reinforcing material and a resin.

Citation Information

Patent Citations

  • Method for controlling welding between metal and polymers through detection of down force

    CN109807460A

  • Continuous steamed rice producing apparatus

    JP1986002813A

  • Composite porous body

    JP2007008762A

  • Manufacturing method of composite porous material

    JP2007012863A

  • Method and apparatus for joining resin and metal together

    JP2010046831A